Implementasi Nilai-Nilai Akhlak Tasawuf dalam Pembelajaran Pendidikan Agama Islam - Faisal M. Nur (LaKaspia, 2025)
Islamic Religious Education (IRE) learning is not merely oriented toward the acquisition of religious knowledge but also plays a strategic role in shaping students’ character and morality. One relevant approach to strengthening the affective and spiritual dimensions of learning is the integration of Sufi moral values (akhlak tasawuf) into the instructional process. This article aims to analyze the implementation of Sufi moral values in IRE learning, including sincerity (ikhlas), patience (sabar), humility (tawadhu’), asceticism (zuhud), and love for God (mahabbah). This study employs a qualitative descriptive approach using a library research method based on classical and contemporary literature related to Sufism, Islamic education, and IRE learning. The findings indicate that Sufi moral values can be systematically integrated through instructional planning, the habituation of religious attitudes, teacher role modeling, and spiritual reflection activities in the IRE learning process. The implementation of these values contributes positively to the formation of students’ religious character, the strengthening of spiritual awareness, and the development of moderate religious attitudes